2013
DOI: 10.1186/1471-244x-13-221
|View full text |Cite
|
Sign up to set email alerts
|

Impact of atypical long-acting injectable versus oral antipsychotics on rehospitalization rates and emergency room visits among relapsed schizophrenia patients: a retrospective database analysis

Abstract: BackgroundAmong schizophrenia patients relapsed on an oral antipsychotic (AP), this study compared the impact of switching to atypical AP long-acting injectable therapy (LAT) versus continuing oral APs on hospitalization and emergency room (ER) visit recurrence.MethodsElectronic records from the Premier Hospital Database (2006-2010) were analyzed. Adult patients receiving oral APs during a schizophrenia-related hospitalization were identified and, upon relapse (i.e., rehospitalization for schizophrenia), were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
83
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 35 publications
(41 reference statements)
8
83
0
Order By: Relevance
“…In contrast, two prospective studies comparing LAI FGAs with various oral SGAs found the oral SGAs to be associated with lower risk of readmission and higher odds ratio of achieving remission compared with LAIs [Conley et al 2003;Haro et al 2006Haro et al , 2007. In the same vein, the electronic records of patients medicated with LAI SGAs were compared with oral APs over a 30-month period revealed that LAI SGAs were associated with significantly lower mean number of rehospitalizations, emergency room visits and fewer hospitalization days compared with oral APs [Lafeuille et al 2013].…”
Section: Long-acting Injectable Versus Oral Ap Formulationsmentioning
confidence: 99%
“…In contrast, two prospective studies comparing LAI FGAs with various oral SGAs found the oral SGAs to be associated with lower risk of readmission and higher odds ratio of achieving remission compared with LAIs [Conley et al 2003;Haro et al 2006Haro et al , 2007. In the same vein, the electronic records of patients medicated with LAI SGAs were compared with oral APs over a 30-month period revealed that LAI SGAs were associated with significantly lower mean number of rehospitalizations, emergency room visits and fewer hospitalization days compared with oral APs [Lafeuille et al 2013].…”
Section: Long-acting Injectable Versus Oral Ap Formulationsmentioning
confidence: 99%
“…We believe these are reasonable indicators of patient relapse as the psychiatric disorders included in the study are often linked to extreme symptoms and behaviours including: psychosis, suicidal ideation, violence, drug abuse and others, all of which warrant medical attention (Lafeuille et al, 2013;Chapman et al, 2015;Hogarty and Ulrich, 1998). Repeated relapses in patients has been shown to increase the risk for shorter remission periods and higher severity of future episodes (Su et al, 2009;Sheperd et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have exhibited a reduction in healthcare resource utilization in schizophrenic patients treated with LAI medication (Lafeuille et al, 2013;Koczerginski & Arshoff, 2011;Su et al, 2009;Davis, 1975;Sena et al, 2003;Olivares et al, 2009;Sheperd et al, 1989). At Lakeridge Health Oshawa (LHO), a midsized community hospital in Oshawa, Ontario, Canada, a group of patients with disorders associated with psychosis were switched from OA treatment to LAI regimens, and multiple drug types were included.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations